Contribución de los espacios artísticos culturales a la construcción de ciudadanía en adolescentes de la ciudad de Huamachuco, La Libertad - 2014 - Cárdenas Carbajal, Lady Kelly (2017)
ABSTRACT This Thesis entitled "Contribution of cultural art spaces in building citizenship in adolescents in the Huamachuco city, La Libertad - 2014" was based on identifying and describing the cultural art spaces of the city of Huamachuco, cultural artistic practices that develop adolescents and describe, thus enabling explain how these cultural art spaces contribute to the construction of citizenship in adolescents in the city of Huamachuco. Research has populations of 228 adolescents and as shown 196 of them. For these research the methods were used Hypothetical - Deductive, Ethnographic method, statistical method and analytic-synthetic method, techniques as observation, literature review, signing, interview, survey, and instruments as fieldbook, tokens, digital camera, video recorder, computer, interview’s questionnaire and survey’s questionnaire; all these allowed the gather information, as well as processing and subsequent analysis. According to the results it was determined that the cultural art spaces of the Huamachuco city contribute positively in the construction of citizenship in teenagers, creating conditions for the expression of artistic skills, recognizing them socially and encouraging the excercise of laws and excercise the civic values.